Experimental Study of Heat Transfer Characteristics in The Hair-Pin Heat Exchanger - Aulia Arif Shalihuddin; Teguh Hady Ariwibowo; Prima Dewi Permatasari (Seminar Nasional Teknik Kimia Kejuangan, 2016)
The heat transfer characteristics in the horizontal Hair-pin heat exchanger are investigated experimentally. Heat transfer coefficients were calculated and plotted with the experimental data. The inner and outer diameters of the inner tube are 10.67 and 12.09 mm. The inner tube is made from stainless steel with thickness 0.71 mm and the length of 500 mm with conductivity thernal 14.4 W/m.K. The outer tube is made from PPMA(polymethyl methacrylate) with thickness 2.27 mm and the length of 450 mm. Cold and hot water are used as working fluids in outer tube and inner tube, respectively. Flows in the inner tube and outer tube were counter flow. The mass flow rates were varied of cold water are 0.0167, 0.0194, 0.0222, 0.025 and 0.0278 kg/s. Reynolds number were got between of 1667 and 2776 in laminar flow to turbulent flow. Then, the results data of cold water are heat transfer 139,67 Watt for the lowest flowrate and 348,78 Watt for the highest flowrate. From the experimental results obtained heat transfer characteristics in Hair-pin heat exchanger, can be increased by varied the mass flow rate in cold side